Возможности теплосбережения в системе транспорта тепловой энергии - Кузнецов Г. В. Гений Владимирович; Озерова И. П. Ирина Петровна; Половников В. Ю. Вячеслав Юрьевич; Цыганкова Ю. С. Юлия Сергеевна (2011, 2011)
Заглавие с титульного листа